Enhancing the spatial awareness of trainee submariners using 3D game engines as training tools. (24th November 2010) - Garrett, Michael; McMahon, Mark
Three-dimensional (3D) gaming technologies can be used to create experiential based learning environments that realistically represent real world places. Such learning environments are well suited for cognitive tasks that include navigation and locomotion in three dimensional environments (Munro et al., 2002). This paper reports on a study to explore the effectiveness of the Location and Scenario Training System (LASTS) to enhance the spatial awareness of trainee submariners. The simulation was used to engage participants in a simplified version of the 12 point safety round (12 PSR) performed inside the main generator room (MGR) on a Royal Australian Navy Collins class submarine. Results indicated that LASTS trainees performed the simplified 12 PSR more effectively than non-LASTS trainees. There was also some evidence to suggest that LASTS trainees possessed a comparatively better overall spatial representation of the MGR, including the development of higher order spatial knowledge.